X(x + 3) + 34 = (x + 5)(x + 2)
First, expand to remove parentheses.
Second, add '2x + 5x' to get '7x'.
Third, cancel out '
![x^{2}](https://tex.z-dn.net/?f=%20x%5E%7B2%7D%20)
' on both sides.
Fourth, subtract '3x' from both sides.
Fifth, subtract '7x - 3x' to get '4x'.
Sixth, subtract '10' from both sides.
Seventh, subtract '34 - 10' to get '24'.
Eighth, divide both sides by '4', leaving the 'x' by itself.
Ninth, since '24 ÷ 4 = 6', simplify the fraction to '6'.
Tenth, switch your sides to get the answer.
![x = 6](https://tex.z-dn.net/?f=x%20%3D%206)
Answer:
x = 6
first function 2nd function
slope =(y2-y1)/(x2-x1) slope =(y2-y1)/(x2-x1)
=(14-2)/(3-0) m = (-3--12/(3-0)
12/3 m=(-3+12)/3
4 m =9/3 =3
y = 4x+2 y = 3x+-12
set these two equations equal
4x+2 = 3x-12
subtract 3x
x+2 = -12
subtract 2 from each side
x = -14
y = 3x-12
y =3*(-14)-12
y = -42-12
y = -54
ChoiceD
Answer:B
Step-by-step explanation:
He charged the man $25.75 for each hour and he worked for 3 hours so multiply $25.75 x 3 = $77.25
The answer is 3x-x :)
You just simplify the expression, (4x^2-x^2) - (x- (-2x))
Answer:
x< -1/4
Step-by-step explanation:
- 3/5 x + 1/5 > 7/20
Subtract 1/5 from each side
- 3/5 x + 1/5-1/5 > 7/20-1/5
-3/5x > 7/20 -1/5
Get a common denominator
-3/5x > 7/20 -1/5*4/4
-3/5x > 7/20 -4/20
-3/5x> 3/20
Multiply by -5/3 to isolate x
Remember that flips the inequality
-5/3* -3/5 x < 3/20*-5/3
x < -1/4